Analysis of The Key Psychological Factors Influencing The Managerial Effectiveness of Department Heads in Higher Education Institutions - Kimyokhon Abdujalilovna Mamatkulova (Indonesian Journal Publisher, 2025)
This article presents an in-depth analysis of the key psychological factors influencing the managerial effectiveness of department heads in higher education institutions. Within the scope of the study, the leader's emotional intelligence, social perception, level of social trust, communicative competence, and reflective abilities in decision-making are examined as critical determinants of managerial success. Drawing upon the theoretical frameworks of contemporary psychologists such as Goleman, Bandura, Luthans, Bass, and Boyatzis, the article scientifically explores the interrelationship between psychological factors and management effectiveness. It also highlights how these factors affect internal institutional dynamics such as the social environment, subordination, power distance, stress tolerance, and awareness of social roles. Based on empirical research, the study underscores the importance of the effective utilization of psychological resources in achieving successful leadership among department heads. The article holds both scientific and practical significance for improving the quality of leadership in higher education